Macrodystrophia lipomatosa: Clinical and radiological insights into localized gigantism - Nishtha Manuja, MBBS; Sandip Mohale, MBBS, DNB Medicine; Shreya Khandelwal, MBBS; Anshul Sood, MBBS (Radiology Case Reports)
A rare type of localized gigantism known as macrodystrophia lipomatosa is characterized by a disproportionate increase in fibroadipose tissues and a gradual overgrowth of all mesenchymal elements. The distribution in the lower extremities’ plantar nerves and the upper extremity's median nerve is most commonly observed. This abnormality is congenital and typically manifests at birth or during the neonatal stage. This deformity begins to mechanically impair joint function, blood supply, and innervation as age advances. The findings from radiography include lucencies in the soft tissues and expansion of the digit's phalanges and soft tissue components, with predominantly distal component involvement. Herein, we present a case of a 20-year-old male from rural India who came to us with the complaint of abnormal asymmetrical swelling of bilateral hand fingers, which has been progressing since birth. Physical examination revealed a soft, non-fluctuant, non-pulsatile swelling with no associated trauma or injury. The clinical picture revealed disproportionate enlargement of phalanges in both hands.